The Effect of Debt Financing and Equity Financing on Expense Ratio Profit - Deni Sunaryo (Yayasan Ilomata, 2021)
This study aims to determine the effect of Debt Financing and Equity Financing on the Profit Expense Ratio. The population in this study is Sharia Commercial Banks registered in Bank Indonesia from 2011 to 2018 as many as 11 banks while the sample is determined by the purposive sampling method and meets the criteria of 2 companies. The analytical method used is multiple linear regression models. This method is also called quantitative because the research data is in the form of numbers and analysis using statistics. Regression analysis results obtained an f-value of 4.155 which means that simultaneously has a significant effect on the profit expense ratio. Partial test results with the t-test showed that debt financing was obtained t-value 1,803> t table 1,687 and significant 0.009 <0.05. then it can be said that debt financing has a significant effect on the profit expense ratio. For equity financing obtained t-value 2.913> t table 1.687 and significant 0.045 <0.05. then it can be said that equity financing has a significant effect on the profit expense ratio.